Emergency management in primary health care clinics in the Northern region of Saudi Arabia: cross-sectional study - Basnawi, Abdullah M.; Koshak, Ahmad K. (Frontiers in Public Health, 2025)
BackgroundPrimary Health Care (PHC) clinics are vital for initial medical emergency management. This study aimed to assess emergency management in PHC clinics in the Northern region of Saudi Arabia by evaluating the availability and utilization of essential equipment, healthcare providers’ training and experience, perceived challenges, and patient referral patterns during emergencies.MethodologyThis cross-sectional study utilized a structured questionnaire to collect data from 40 healthcare professionals conveniently sampled from Primary Health Care (PHC) clinics in the Northern region of Saudi Arabia. Data were analysed using descriptive statistics, alongside bivariate (Chi-squared) and multivariable (binary logistic regression) inferential tests to examine determinants of preparedness.ResultsThe study found that while essential equipment like AEDs and nebulizers were available in many clinics, the availability of certain critical items, such as antidotes for common poisons, was notably limited. A significant proportion of healthcare providers had received BLS training, but the prevalence of advanced training (ACLS, PALS) was lower, with “lack of staff training or experience” being the most significant challenge. High patient referral rates were primarily due to the severity of conditions, need for advanced procedures, and lack of on-site equipment. Crucially, inferential analyses revealed that governmental clinic status and the presence of paramedics were significant independent determinants of adequate emergency preparedness.ConclusionThis study highlights significant gaps in advanced training and specialized equipment, underscoring an urgent need for targeted policy and procedural interventions within PHC clinics in the Northern region of Saudi Arabia.